Intracategorial Varieties of Contempt in a Heterogeneous Sample - Delgado, Ana R.; Universidad de Salamanca, Spain (2012)
Consistent with current emotion theory, we should note that contempt is not a homogeneous category but rather shows intracategorial variability. Previous research on Spanish samples shows a communicative structure in which contempt is felt towards intimate, social or abstract receivers, for reciprocal, altruistic or prejudiced reasons. Our objective was to test, on a large and heterogeneous sample, the previously found structure and variations of the experience of contempt as well as its spontaneous facial expression. Testing the association of contempt varieties with certain subject attributes was a secondary goal. Results from 130 participants from the Spanish general population corroborated the previously found structure and varieties, as well as the associations between contempt receiver and attribution. No relation was found with sex, age or emotion recognition ability. As to spontaneous facial expression, disgust was more often expressed by those who narrated their personal episodes of contempt for reciprocal reasons, and was less often expressed by the people who described prejudiced scenarios. This result indicates that the conventionally considered facial expression of contempt is not the only one, as already stated by Darwin, and should not be considered as such by experimental and psychometric procedures.